Paying Taxes 2011 : The Global Picture - World Bank; International Finance Corporation; PwC (World Bank, Washington, DC, 2017)
Taxes are the price you pay for civilization. Taxes provide government revenues, and those who pay them have a stake in the system and in how government spends its money. Taxes are lifeblood of a stable and prosperous society. In the wake of the global economic downturn levying tax in even more difficult. With large structural deficits in the big developed economies, fiscal policy has never been under so much public scrutiny. While there is a clear expectation that economies will need to raise taxes as well as making spending cuts, they will need to remain cautious in how they raise taxes to ensure that recovery is not stifled. For developing economies, with cuts in aid budgets, tax revenues may prove to be a more sustainable source of financing. But challenges remain in terms of combating capital flight. Reducing the size of the informal economy and helping tax authorities to monitor compliance and collect taxes.